Strong entrepreneurial focus and internationalization - the way to success for Finnish ice hockey: the case of JYP ice hockey team - Ahonen, A. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
Ice hockey is the most professionalized sport in Finland, and it has had an important effect on the overall sports development in Finland. The national ice hockey league was the first league to professionalize in Finland, and it is the most widely followed sport in terms of spectator numbers and media coverage. Internationalization and entrepreneurship have played a remarkable role in the development of Finnish ice hockey. Internationalization has been influenced, first, by the North American National Hockey League (NHL), and later by the Russian Kontinental Hockey League (KHL) and Europe`s Champions Hockey League (CHL). The establishment of entrepreneurially driven limited companies amongst ice hockey leagues at the turn of the century was a pivotal point for professionalization and commercialization in Finnish ice hockey. The aim of this study is to examine the impact of internationalization on one successful entrepreneurially driven Finnish ice hockey club, JYP ice hockey team, by demonstrating its path from a small-town club to a multi-time Finnish Champion and Finland`s first European Trophy (2014) and Champions Hockey League (2018) winner.